Estimating the causal effects of genetically predicted plasma proteome on heart failure - Yang, Jian; Yan, Bin; Zhang, Haoxuan; Lu, Qun; Yang, Lihong; Liu, Ping; Bai, Ling (Frontiers in Cardiovascular Medicine, 2023)
Background: Heart Failure (HF) is the end-stage cardiovascular syndrome with poor prognosis. Proteomics holds great promise in the discovery of novel biomarkers and therapeutic targets for HF. The aim of this study is to investigate the causal effects of genetically predicted plasma proteome on HF using the Mendelian randomization (MR) approach. Methods: Summary-level data for the plasma proteome (3,301 healthy individuals) and HF (47,309 cases; 930,014 controls) were extracted from genome-wide association studies (GWASs) of European descent. MR associations were obtained using the inverse variance-weighted (IVW) method, sensitivity analyses, and multivariable MR analyses. Results: Using single-nucleotide polymorphisms as instrumental variables, 1-SD increase in MET level was associated with an approximately 10% decreased risk of HF (odds ratio [OR]: 0.92; 95% confidence interval [CI]: 0.89 to 0.95; P = 1.42 × 10−6), whereas increases in the levels of CD209 (OR: 1.04; 95% CI: 1.02–1.06; P = 6.67 ×10−6) and USP25 (OR: 1.06; 95% CI: 1.03–1.08; P = 7.83 ×10−6) were associated with an increased risk of HF. The causal associations were robust in sensitivity analyses, and no evidence of pleiotropy was observed. Conclusion: The study findings suggest that the hepatocyte growth factor/c-MET signaling pathway, dendritic cells-mediated immune processes, and ubiquitin-proteasome system pathway are involved in the pathogenesis of HF. Moreover, the identified proteins have potential to uncover novel therapies for cardiovascular diseases.